2016
DOI: 10.13075/ijomeh.1896.00620
|View full text |Cite
|
Sign up to set email alerts
|

Work-related musculoskeletal disorders among physical therapists: A comprehensive narrative review

Abstract: Healthcare workers, especially those with direct patient contact are amongst professions with the highest rate of workrelated musculoskeletal disorders (WMSDs), physical therapists (PTs) being one of them. Our objective was to review current knowledge relating to the prevalence, risk factors and prevention of WMSDs among PTs. Pubmed, Google Scholar and PEDro databases were searched for terms relating to WMSDs in PTs from inception to 2015. The prevalence of WMSDs among PTs was high, with lifetime prevalence re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
2
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 24 publications
3
56
2
3
Order By: Relevance
“…Even if the values recorded on the fishing vessels did not exceed the action level (0.5 m/s 2 ) established by the European Directive, workers were subjected to constant muscle tension. Several studies demonstrate that awkward body positions which increase muscle tension during working activities contributes to the onset of musculoskeletal disorders [60][61][62]. This phenomenon is due to excessive force on the joints and overload the muscles and tendons around the articulation performed.…”
Section: Discussionmentioning
confidence: 99%
“…Even if the values recorded on the fishing vessels did not exceed the action level (0.5 m/s 2 ) established by the European Directive, workers were subjected to constant muscle tension. Several studies demonstrate that awkward body positions which increase muscle tension during working activities contributes to the onset of musculoskeletal disorders [60][61][62]. This phenomenon is due to excessive force on the joints and overload the muscles and tendons around the articulation performed.…”
Section: Discussionmentioning
confidence: 99%
“…According to the European Foundation for the Improvement of Living and Working Conditions, MSDs are the main occupational disease suffered by European workers and account for more than 50% of serious work-related diseases [1]. Furthermore, it has been widely reported that MSDs are particularly prevalent and among the most common health complaints in health care workers and especially in hospital staff and among nurses and physical therapists [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…A mesma é dividida em dois tipos, são elas: dependente ( existe a necessidade do auxílio, de uma ou mais pessoas ou um dispositivo assistivo) e independente (a função motora deve ser capaz de suportar o peso dos membros inferiores), sendo definido pelo nível de lesão, escolha do sujeito, ajudas utilizadas e segurança para transferir (ALONSO, 2011). Essa atividade de transferência de sujeitos, apresenta-se de forma complicada e exaustiva, considerando o alto esforço físico realizado pelo sistema musculoesquelético dos envolvidos no processo, estando assim conectado ao risco de patologias e problemas lombares (MILHEM et al, 2016;KING et al,2009).…”
Section: Atividade De Transferênciaunclassified